Revitalising Al-Qur'an Learning Through Calligraphy: An Integrative Study At TPQ Saleh Hambali Jayapura - Kahfi, Sahibul Kahfi; Zulihi, Zulihi; Hidayat, Topan (Universitas Islam Sultan Agung, 2025)
Studies on Qur’anic learning in TPQ institutions tend to rely on traditional methods that focus solely on repetition of memorization and recitation, without incorporating innovative or creative approaches. This study aims to analyze the integration of calligraphy in Qur’anic learning, its impact on students’ interest and learning motivation, and its contribution to the development of religious character. This research employs a qualitative descriptive method, using interviews, observation, and documentation as data collection techniques, and data analysis based on the Miles and Huberman model. The findings reveal that (1) the integration of calligraphy in Qur’anic learning is proven to be effective in improving the quality of the learning process, as it provides students with a more meaningful, visual, and enjoyable learning experience; (2) calligraphy integration can enhance students’ interest in learning, as reflected in their increased enthusiasm, active participation, and motivation during Qur’anic lessons; and (3) the integration of calligraphic art contributes to the development of students’ religious character, marked by the emergence of perseverance, discipline, and a deepened love for the Qur’an. These findings affirm that integrating artistic elements into Qur’anic learning can generate positive cognitive, affective, and spiritual outcomes.